Interposing Prolene Mesh Repair For Upper Abdominal Wall Defects - Bhathena, Dr. Hosi M.; Kavarana, Dr. Naozer M. (Indian Journal of Plastic Surgery, 1992)
Dermatofibrosarcoma, Supra umbilical excisional defect with a deficit of 4 cms. of left rectus abdominis was repaired. Results are presented.
Keywords: Rectus abdominis Deficit